2016
DOI: 10.2473/journalofmmij.132.114
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Recycling of Rhenium and Process Technologies

Abstract: レニウム (Re) は高融点 (3453 K) かつ高弾性率 (室温で 460 GPa) を有するレアメタルである 1) 。特定の金属に Re を添加する Rhenium (Re) is used as an additive in several alloys, such as nickel-based superalloys for jet engine turbine blades, platinum catalysts for oil refining, and thermocouples used at ultra-high temperature, in order to improve strength and stability at high temperature. Due to the rare and unevenly distributed nature of Re, there is risk of supply disruption owing to supply shortage and the rapid increase in Re price. To minimize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Anderson et al (2013) reviewed the commercial processing technologies of extracting rhenium from primary and secondary sources. Yagi and Okabe reviewed the smelting technologies of recovering rhenium from various ores (Yagi and Okabe, 2016a), the characteristics of Re-containing materials, and the current Re recycling status and technologies (Yagi and Okabe, 2016b), but both in Japanese. Wang and Wang (2018) reviewed the recent processes of separating and enriching rhenium in China.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson et al (2013) reviewed the commercial processing technologies of extracting rhenium from primary and secondary sources. Yagi and Okabe reviewed the smelting technologies of recovering rhenium from various ores (Yagi and Okabe, 2016a), the characteristics of Re-containing materials, and the current Re recycling status and technologies (Yagi and Okabe, 2016b), but both in Japanese. Wang and Wang (2018) reviewed the recent processes of separating and enriching rhenium in China.…”
Section: Introductionmentioning
confidence: 99%
“…For details on the technologies for Re smelting and recycling and for its recovery from superalloys, please also refer to the previous reports of the authors. [14][15][16] Demand for rhenium Re is often used as an alloying element in Ni-based superalloys, which are employed in aircraft engines, and the alloys used for ultrahigh-temperature thermocouples to improve their high-temperature strengths and creep resistances.…”
Section: Introductionmentioning
confidence: 99%
“…For details on the technologies for Re smelting and recycling and for its recovery from superalloys, please also refer to the previous reports of the authors. 14–16…”
Section: Introductionmentioning
confidence: 99%
“…7) The different recycling techniques are applied to revert superalloys depending on the amounts of impurities, such as remelting, downgraded use and hydrometallurgy process. 8) Revert superalloys with a few impurities are usually remelted with virgin superalloys. Pu et al 9) found that there is a large fluctuation range of compression and yield strength at 25°C due to the increased quantity and size of Al 2 O 3 inclusion by the addition of revert GH4169 alloy.…”
Section: Introductionmentioning
confidence: 99%